HOLISTIC MARKETING IN THE SYSTEM OF STRATEGIC MANAGEMENT AND MARKET ORIENTATION OF MODERN ENTERPRISES - Bondarenko, Valerii; Kovalenko, Nataliia; Barylovych, Olena (Current Problems of Sustainable Development, 2026)
The article is devoted to the study of global business space transformations under the influence of digitalization and competitive pressure, due to which traditional fragmented promotion tools lose their effectiveness. It is substantiated that such trends force companies to transition to strategic planning, which significantly actualizes the importance of holistic marketing as an integrated management concept capable of ensuring the long-term sustainability of modern organizations. The purpose of the article is a comprehensive substantiation of the principles of integrating holistic marketing into the strategic management system of enterprises, along with modeling an implementation architecture that takes into account market orientation and ambidextrous business performance. The information base of the study comprises the works of leading experts in the fields of management and marketing. The research methodology is based on the use of methods of systemic, logical, and comparative analysis, analysis and synthesis, generalization, as well as structural modeling of business processes. The study substantiates the expediency of transitioning from isolated commercial functions to an end-to-end business philosophy that unites all organizational units around value creation. The nature of the impact of holistic marketing on the stages of market orientation is determined: relationship marketing stimulates data collection, internal marketing ensures its distribution between departments, integrated marketing drives a collaborative response to environmental demands, and socially responsible marketing acts as a general ethical and legal regulator of the cycle. It is proved that the comprehensive deployment of holistic approach ensures ambidextrous performance, allowing the company to maintain a stable balance between the exploitation of existing resources and the exploration of innovative niches. The scientific novelty of the work lies in developing an original three-level stack integration model that sequentially coordinates internal culture, the interaction of key departments of the enterprise, and external partner networks under a single socio-ethical contour to completely eliminate information barriers.